Friction body material, preparation method thereof and composition brake shoe

By using the synthetic gate shoe prepared with specific composition of friction body materials and processes, the heat resistance and service life of traditional gate shoe under high-speed and heavy-load train operation conditions is solved, and a higher friction coefficient and lower wear amount are achieved, reducing the maintenance cost of railway trucks.

CN119899486APending Publication Date: 2025-04-29SHENHUA RAIL & FREIGHT WAGONS TRANSPORT
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510003458.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

Traditional synthetic gate shoes show poor heat resistance and short service life under high-speed and heavy-duty train operating conditions, and are prone to metal inlay damage to truck wheels in growing ramps and humid environments, resulting in an increase in replacement frequency and an increase in maintenance costs.

Method used

A friction body material including bonding materials, reinforcement materials, filler materials and auxiliary materials is used to prepare it into a synthetic gate shoe through a specific stirring and refining process to improve the hardness, impact strength and friction coefficient of the gate shoe, and adapt to the braking wear performance requirements of railway general trucks with different axle weights and operating speeds.

Benefits of technology

The hardness, impact strength and friction coefficient of the synthetic gate shoe are controlled, which improves the heat resistance and service life of the gate shoe, reduces the wear and noise under different working conditions, and reduces the maintenance cost of railway trucks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005226147310000111
    Figure BDA0005226147310000111
  • Figure BDA0005226147310000121
    Figure BDA0005226147310000121
  • Figure BDA0005226147310000141
    Figure BDA0005226147310000141
Patent Text Reader

Abstract

The invention provides a friction body material, a preparation method thereof and a composition brake shoe, and relates to the technical field of composition brake shoes for railway heavy-duty trucks. The friction body material comprises the following components or is prepared from the following raw materials in parts by weight: 46-68 parts of a bonding material; 48-88 parts by weight of a reinforcing material; 97 to 167 parts by weight of a filling material; the bonding material comprises phenolic resin and powdered nitrile rubber, and the auxiliary material comprises ethanol and octadecenoic acid. According to the friction body material provided by the invention, control on performance indexes such as hardness and impact strength of the composition brake shoe is realized, and an ideal friction coefficient is obtained so as to meet the requirements of railway general-purpose trucks with different axle loads and running speeds on brake abrasion performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of synthetic brake shoes for railway heavy-duty freight cars, and in particular to a friction body material and a preparation method thereof, and a synthetic brake shoe. Background Art

[0002] According to relevant statistics from the National Railway Administration, the number of railway freight cars in China will be 1.005 million in 2024, of which 854,000 are general-purpose railway freight cars, accounting for 85%. In order to ensure that general-purpose railway freight cars can stop safely within the specified braking distance, brake shoes are usually used to hold the wheel tread tightly during braking, and the friction force is used to stop the wheels of the freight cars from rotating. Since the 1940s, the development of railway freight car brake shoes has undergone an evolution from cast iron brake shoes, powder metallurgy brake shoes, to synthetic brake shoes. After years of actual loading and use, cast iron brake shoes and powder metallurgy brake shoes have been gradually eliminated due to their high manufacturing cost, unstable friction coefficient, high environmental pollution and serious wear on freight car wheels.

[0003] In order to overcome the above performance defects, many countries have started the research work of synthetic brake shoes since the 1940s, and my country also started to develop synthetic brake shoes in the 1950s. Compared with traditional brake shoes, synthetic brake shoes have the advantages of low manufacturing cost, adjustable friction coefficient, environmental protection and little wear on truck wheels. In recent years, with the development of the national economy, in order to improve the efficiency of railway freight and reduce transportation costs, the technology of high-speed and heavy-duty general-purpose trucks has developed rapidly. The braking friction and wear performance of synthetic brake shoes manufactured by traditional formulas and preparation methods cannot match the operating conditions of high-speed and heavy-duty trains. They have poor heat resistance and short service life during use. Under special braking conditions such as long and long slopes and humid environments, brake shoes are prone to metal inlay damage to truck wheels and other problems, which increases the frequency of replacement of railway truck brake shoes and increases the maintenance cost of railway trucks. Summary of the invention

[0004] In view of the above analysis, the present invention aims to provide a friction body material and a preparation method thereof and a synthetic brake shoe to solve at least one of the following existing problems: improving the friction and wear performance of the synthetic brake shoe, and improving the mechanical properties of the synthetic brake shoe.

[0005] The purpose of the present invention is mainly achieved through the following technical solutions:

[0006] In a first aspect, the present invention provides a friction material, comprising the following components or made of raw materials comprising the following components:

[0007] Adhesive material: 46-68 parts by weight;

[0008] Reinforcement material: 48-88 parts by weight;

[0009] Filling material: 97-167 parts by weight;

[0010] Auxiliary materials: 1.5-9 parts by weight,

[0011] Wherein, the bonding material comprises phenolic resin and powdered nitrile rubber, and the auxiliary agent comprises ethanol and octadecenoic acid.

[0012] Preferably, the amount of the adhesive material is 54-60 parts by weight.

[0013] Preferably, the amount of the reinforcing material is 62-76 parts by weight.

[0014] Preferably, the amount of filler material used is 118-147 parts by weight.

[0015] Preferably, the dosage of auxiliary agents and excipients is 4-7.5 parts by weight.

[0016] Preferably, in the friction body material, the amount of phenolic resin used is 23-34 parts by weight, preferably 27-30 parts by weight; the amount of powdered nitrile rubber used is 23-34 parts by weight, preferably 27-30 parts by weight.

[0017] Preferably, the hexamethylenetetramine content of the phenolic resin is 7wt.%-8wt.%, the free phenol content is ≤1wt.%, the polymerization time at 150°C is 40-70s, and the particle size is 150-250 meshes.

[0018] Preferably, the powdered nitrile rubber has a bound acrylonitrile content of 36wt.%-40wt.%, and a particle size of 35-45 mesh.

[0019] Preferably, in the friction body material, the amount of ethanol used is 1-6 parts by weight, preferably 3-5 parts by weight; the amount of octadecenoic acid used is 0.5-3 parts by weight, preferably 1-2.5 parts by weight.

[0020] Preferably, the reinforcing material includes at least one of sepiolite, steel fiber, mineral fiber, and needle-shaped wollastonite.

[0021] Preferably, the reinforcing material comprises sepiolite, steel fiber, mineral fiber and needle-shaped wollastonite, wherein:

[0022] The amount of sepiolite is 25-35 parts by weight, preferably 28-32 parts by weight;

[0023] The amount of steel fiber is 10-20 parts by weight, preferably 14-17 parts by weight;

[0024] The amount of mineral fiber is 6-16 parts by weight, preferably 10-13 parts by weight;

[0025] The amount of needle-shaped wollastonite used is 7-17 parts by weight, preferably 10-14 parts by weight.

[0026] Preferably, the filling material includes at least one of calcium carbonate, barium sulfate, reduced iron powder, graphite, high aluminum powder, potassium feldspar, molybdenum disulfide and antimony trisulfide.

[0027] Preferably, the filling material includes calcium carbonate, barium sulfate, reduced iron powder, graphite, high aluminum powder, potassium feldspar, molybdenum disulfide and antimony trisulfide, wherein:

[0028] The amount of calcium carbonate is 5-15 parts by weight, preferably 8-12 parts by weight;

[0029] The amount of barium sulfate is 5-15 parts by weight, preferably 8-12 parts by weight;

[0030] The amount of reduced iron powder is 21-31 parts by weight, preferably 24-28 parts by weight;

[0031] The amount of graphite is 4-14 parts by weight, preferably 8-11 parts by weight;

[0032] The amount of high aluminum powder is 11-21 parts by weight, preferably 14-18 parts by weight;

[0033] The amount of potassium feldspar is 48-58 parts by weight, preferably 51-55 parts by weight;

[0034] The amount of molybdenum disulfide is 2-8 parts by weight, preferably 3-7 parts by weight;

[0035] The amount of antimony trisulfide used is 1-5 parts by weight, preferably 2-4 parts by weight.

[0036] In a second aspect, the present invention provides a method for preparing the friction body material, comprising the following steps:

[0037] Step 1: Stirring the bonding material including phenolic resin and powdered nitrile rubber for the first time, and then adding reinforcing material and filling material and stirring for the second time;

[0038] Step 2: Carry out the first stage of internal mixing, then add auxiliary agents and materials to carry out the second stage of internal mixing, and then discharge the material.

[0039] Preferably, in step 1, the duration of the first stirring and the second stirring are the same or different, and are each independently 2-5 min.

[0040] Preferably, in step 2, the conditions for the first stage of banburying include: a rotation speed of 20-30 rpm, preferably 24-27 rpm; a pressure of 0.2-0.4 MPa, preferably 0.25-0.35 MPa, and a banburying time of 120-180 s.

[0041] Preferably, in step 2, the conditions for the second stage of internal mixing include: a rotation speed of 20-30 rpm, preferably 24-27 rpm; and a pressure of 0.2-0.4 MPa, preferably 0.25-0.3 MPa.

[0042] Preferably, in step 2, the temperature of the discharged glue is 40-50°C, preferably 42-45°C.

[0043] In a third aspect, the present invention provides a synthetic brake shoe, comprising a friction body material and a shoe back, wherein the friction body material is fixed on the shoe back.

[0044] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:

[0045] A) The friction material provided by the present invention can realize the control of performance indicators such as hardness and impact strength of synthetic brake shoes, and obtain an ideal friction coefficient to meet the requirements of brake wear performance of general railway freight cars with different axle weights and running speeds.

[0046] B) The preparation method of the friction body material provided by the present invention performs the first stirring through the bonding material, and fully wraps the cross-linked nitrile powder with thermoplastic phenolic resin, which can effectively prevent the cross-linked nitrile powder from agglomerating during the banburying process and improve the banburying vulcanization quality of the material; the banburying process enables the synthetic brake shoe to have good heat resistance and be able to adapt to the continuous high temperature generated during the braking process, and the performance of the brake shoe wheel tread will not drop sharply due to the temperature increase.

[0047] C) The synthetic brake shoe provided by the present invention is a synthetic brake shoe solidified by the friction body material and the shoe back, which has light weight, stable friction coefficient, small wear, low noise during braking, high mechanical properties, and can be used for heavy-duty railway trucks, fully ensuring the braking friction and wear performance and mechanical properties of the synthetic brake shoe. DETAILED DESCRIPTION

[0048] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0049] In a first aspect, the present invention provides a friction material, comprising the following components or prepared from raw materials comprising the following components:

[0050] Adhesive material: 46-68 parts by weight, preferably 54-60 parts by weight;

[0051] Reinforcement material: 48-88 parts by weight, preferably 62-76 parts by weight;

[0052] Filling material: 97-167 parts by weight, preferably 118-147 parts by weight;

[0053] Auxiliary materials: 1.5-9 parts by weight, preferably 4-7.5 parts by weight,

[0054] Wherein, the bonding material comprises phenolic resin and powdered nitrile rubber, and the auxiliary agent comprises ethanol and octadecenoic acid.

[0055] The friction body material provided by the present invention can realize the control of performance indicators such as hardness and impact strength of synthetic brake shoes, and obtain an ideal friction coefficient to meet the requirements of general railway freight cars with different axle weights and running speeds for brake wear performance.

[0056] It is believed that the bonding material plays a role in bonding other components, so that the friction body material forms a whole and ensures the structural integrity of the brake shoe. In the prior art, liquid nitrile rubber is usually used as the bonding material. Although the processing process of the friction body material using this system material is relatively simple, it needs to be mixed and processed in a liquid state, and usually requires special equipment and technology to control its fluidity. The present invention uses powdered nitrile rubber and phenolic resin as bonding materials, which are easy to disperse in the substrate during processing and can provide a stable friction coefficient, good impact resistance and wear resistance.

[0057] Furthermore, ethanol and octadecenoic acid work synergistically to improve the performance of friction body materials. Among them, octadecenoic acid has good thermal stability. In high-friction synthetic brake shoes, octadecenoic acid can prevent problems such as lubrication failure and increased friction coefficient caused by high temperature. This improvement in thermal stability helps to ensure the normal operation of the brake system in a high temperature environment and improve braking efficiency and safety. During the mixing process, too much octadecenoic acid will cause excessive vulcanization of the material, and too little octadecenoic acid will cause insufficient vulcanization of the material, both of which will affect the material performance.

[0058] In a specific embodiment of the present invention, the amount of phenolic resin used is 23-34 parts by weight, for example, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34 parts by weight, etc., preferably 27-30 parts by weight.

[0059] In a specific embodiment of the present invention, the amount of powdered nitrile rubber is 23-34 parts by weight, for example, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34 parts by weight, etc., preferably 27-30 parts by weight.

[0060] In a specific embodiment of the present invention, the fluidity of the phenolic resin is 35-60 mm, the hexamethylenetetramine content is 7wt.%-8wt.%, the free phenol content is ≤1wt.%, the polymerization time at 150°C is 40-70s, and the particle size is 150-250 mesh, preferably 200 mesh ≥95wt.%.

[0061] In a specific embodiment of the present invention, the powdered nitrile rubber has a combined acrylonitrile content of 36 wt.% to 40 wt.%, and a Mooney viscosity of (ML 100±0.5℃ 1+4) 100-150, particle size is 35-45 mesh, preferably 40 mesh ≥ 95wt.%.

[0062] In a specific embodiment of the present invention, the amount of ethanol used is 1-6 parts by weight, for example, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6 parts by weight, etc., preferably 3-5 parts by weight.

[0063] In a specific embodiment of the present invention, the amount of octadecenoic acid is 0.5-3 parts by weight, for example, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3 parts by weight, etc., preferably 1-2.5 parts by weight.

[0064] In a specific embodiment of the present invention, the ethanol is industrial alcohol, and the alcohol content is ≥95wt.%.

[0065] In a specific embodiment of the present invention, octadecenoic acid is oleic acid, with an acid value (mgKOH / g): 180-195, a saponification value (mgKOH / g): 190-202, and an iodine value (gl / 100g): 70-95.

[0066] In the present invention, the auxiliary agent and auxiliary material can also accelerate the mixing speed of the friction body material, shorten the mixing time, and improve the mixing production efficiency.

[0067] In the present invention, the reinforcing material can enhance the strength, hardness and wear resistance of the friction body material, and improve the wear resistance of the brake shoe during the braking process.

[0068] In a specific embodiment of the present invention, the reinforcing material includes at least one of sepiolite, steel fiber, mineral fiber, and needle-shaped wollastonite. Preferably, the reinforcing material includes sepiolite, steel fiber, mineral fiber, and needle-shaped wollastonite, wherein:

[0069] The amount of sepiolite is 25-35 parts by weight, for example, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35 parts by weight, etc., preferably 28-32 parts by weight;

[0070] The amount of steel fiber is 10-20 parts by weight, such as 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20 parts by weight, etc., preferably 14-17 parts by weight;

[0071] The amount of mineral fiber is 6-16 parts by weight, for example 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16 parts by weight, etc., preferably 10-13 parts by weight;

[0072] The amount of needle-shaped wollastonite used is 7-17 parts by weight, for example, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17 parts by weight, etc., preferably 10-14 parts by weight.

[0073] In a specific embodiment of the present invention, the mineral fiber is selected from basalt fiber, and the fiber length of the mineral fiber is 0.3-0.5 mm, and the fiber diameter is 0.03-0.08 mm.

[0074] In a specific embodiment of the present invention, the specifications of the steel fiber are: 14 mesh: 0-1.0wt.%, 20 mesh: 0-1.5wt.%, 40 mesh: 5-12wt.%, 70 mesh: 5-25wt.%, 100 mesh: 5-20wt.%, bottom of the dish: 55-75wt.%.

[0075] In a specific embodiment of the present invention, the particle size of the sepiolite is 4-6 mm.

[0076] In a specific embodiment of the present invention, the needle-shaped wollastonite is needle-shaped, with a screening rate of 60 mesh ≥95wt.%, aspect ratio: 24:1, SiO2 content ≥48wt.%, CaO content ≥44wt.%, Fe2O3 content ≤1wt.%, Al2O3 content ≤0.8wt.%.

[0077] In the present invention, the filling material is used to adjust the brake friction and wear performance of the brake shoe to ensure that there is a suitable friction coefficient under different working conditions to achieve a stable braking effect. In a specific embodiment of the present invention, the filling material includes at least one of calcium carbonate, barium sulfate, reduced iron powder, graphite, high aluminum powder, potassium feldspar, molybdenum disulfide and antimony trisulfide. Preferably, the filling material includes calcium carbonate, barium sulfate, reduced iron powder, graphite, high aluminum powder, potassium feldspar, molybdenum disulfide and antimony trisulfide, wherein:

[0078] The amount of calcium carbonate is 5-15 parts by weight, for example 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15 parts by weight, etc., preferably 8-12 parts by weight;

[0079] The amount of barium sulfate is 5-15 parts by weight, for example, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15 parts by weight, etc., preferably 8-12 parts by weight;

[0080] The amount of reduced iron powder is 21-31 parts by weight, for example, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31 parts by weight, etc., preferably 24-28 parts by weight;

[0081] The amount of graphite is 4-14 parts by weight, for example 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14 parts by weight, etc., preferably 8-11 parts by weight;

[0082] The amount of high aluminum powder is 11-21 parts by weight, for example, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21 parts by weight, etc., preferably 14-18 parts by weight;

[0083] The amount of potassium feldspar is 48-58 parts by weight, for example, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58 parts by weight, etc., preferably 51-55 parts by weight;

[0084] The amount of molybdenum disulfide is 2-8 parts by weight, such as 2, 3, 4, 5, 6, 7, 8 parts by weight, etc., preferably 3-7 parts by weight;

[0085] The amount of antimony trisulfide used is 1-5 parts by weight, for example, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5 parts by weight, etc., preferably 2-4 parts by weight.

[0086] In a specific embodiment of the present invention, the screening rate of calcium carbonate is: 325 mesh ≥ 95wt.%, and the calcium carbonate content is ≥ 97wt.%.

[0087] In a specific embodiment of the present invention, the screening rate of barium sulfate is: 325 mesh ≥ 95wt.%, and the barium content is ≥ 80wt.%.

[0088] In a specific embodiment of the present invention, the screening rate of high aluminum powder is: 325 mesh ≥ 95wt.%, Al2O3 content ≥ 75wt.%, Fe2O3 content ≤ 2wt.%.

[0089] In a specific embodiment of the present invention, the screening rate of potassium feldspar is: 325 mesh ≥ 95wt.%, SiO2 content ≥ 70wt.%, Al2O3 content ≥ 10wt.%.

[0090] In a specific embodiment of the present invention, the graphite is flake graphite with a carbon content of ≥80wt.%.

[0091] In a specific embodiment of the present invention, in the molybdenum disulfide, the molybdenum disulfide content is ≥98.5wt.%, the oil content is ≤0.19wt.%, the molybdenum anhydride content is ≤0.18wt.%, and the water content is ≤0.15wt.%.

[0092] In a specific embodiment of the present invention, the screening rate of antimony trisulfide is: 200 mesh = 100%, and the antimony content is 69wt.%-73wt.%.

[0093] In the present invention, the addition of molybdenum disulfide and antimony trisulfide can prevent the friction coefficient in the low-speed section from being too high and stabilize the friction coefficient in the high-speed section.

[0094] Although the types and functions of adhesive materials, reinforcing materials, filling materials, and auxiliary materials have been described above, in the present invention, adhesive materials, reinforcing materials, filling materials, and auxiliary materials do not act alone, but work synergistically as an overall friction body material to jointly improve the friction and wear properties and mechanical properties of the friction body material.

[0095] The friction body material provided by the present invention can control the performance indicators such as hardness and impact strength of the synthetic brake shoe, and obtain an ideal friction coefficient to meet the requirements of general railway freight cars with different axle weights and running speeds for brake wear performance.

[0096] In a second aspect, the present invention provides a method for preparing a friction body material, comprising the following steps:

[0097] Step 1: Stirring the bonding material including phenolic resin and powdered nitrile rubber for the first time, and then adding reinforcing material and filling material and stirring for the second time;

[0098] Step 2: Carry out the first stage of internal mixing, then add auxiliary agents and materials to carry out the second stage of internal mixing, and then discharge the material.

[0099] The preparation method of the friction body material provided by the present invention performs the first stirring by bonding materials, and fully wraps the cross-linked powder nitrile with thermoplastic phenolic resin to prevent the cross-linked powder nitrile from agglomerating during the banburying process, so that the banburying process is not affected by the Mooney viscosity index of the cross-linked powder nitrile, and can effectively prevent the cross-linked powder nitrile from agglomerating during the banburying process, thereby improving the banburying vulcanization quality of the material. Compared with the traditional centrifuge stirring process, the banburying process can better improve the uniformity of the brake shoe material, ensure the stability of the brake shoe mechanical properties and friction and wear properties, give full play to the heat resistance of materials such as graphite and antimony trisulfide, so as to adapt to the continuous high temperature generated during the braking process, so that the friction coefficient will not drop sharply due to the temperature increase when the brake shoe is braked. Add auxiliary agents and auxiliary materials in the second banburying stage to accelerate the material banburying speed, shorten the banburying time, improve the banburying production efficiency, and improve the fusion effect of various materials of the friction body.

[0100] It should be noted that, in the present invention, if no auxiliary materials are added, not only will the banburying speed be too slow, but the material will also fail to form banburying particles, the material fusion effect will be reduced, and the mechanical properties of the friction material will deteriorate. In addition, auxiliary materials cannot be added before banburying or during the first stage of banburying, otherwise the uniformity of the material will deteriorate, and the addition of fiber materials will cause agglomeration.

[0101] In the method for preparing the friction body material provided by the present invention, there is no restriction on the duration of the first stirring and the second stirring in step 1, as long as the stirring is uniform, for example, the duration of the first stirring and the second stirring can be the same or different, and each is independently 2-5 minutes. The temperature of the first stirring and the second stirring is room temperature.

[0102] In a specific embodiment of the present invention, in step 2, the conditions of the first stage of banburying include:

[0103] Rotation speed 20-30 rpm, for example 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30 rpm, etc., preferably 24-27 rpm;

[0104] Pressure 0.2-0.4 MPa, for example 0.2, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.3, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.4 MPa, etc., preferably 0.25-0.35 MPa;

[0105] The kneading time is 120-180s, for example, 120, 130, 140, 150, 160, 170, 180s, etc., and the temperature is room temperature.

[0106] In a specific embodiment of the present invention, in step 2, the conditions of the second stage of banburying may be the same as or different from the conditions of the first stage of banburying, and the conditions of the second stage of banburying include:

[0107] Rotation speed 20-30 rpm, for example 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30 rpm, etc., preferably 24-27 rpm;

[0108] The pressure is 0.2-0.4 MPa, for example, 0.2, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.3, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.4 MPa, etc., preferably 0.25-0.35 MPa.

[0109] In a specific embodiment of the present invention, the temperature of the rubber in the second stage of mixing in step 2 is raised to 40-50°C for discharging, for example, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50°C, etc., preferably 42-45°C.

[0110] The preparation method of the friction body material provided by the present invention ensures that the synthetic brake shoe has a stable compression modulus value and a compression strength value by formulating the standards of the internal mixing time and the internal mixing glue temperature, thereby improving the physical and mechanical properties of the brake shoe, ensuring that the synthetic brake shoe maintains stable braking friction and wear performance under extreme braking conditions such as high speed, heavy load, and humidity, and improving the preparation quality of the synthetic brake shoe.

[0111] The friction body material preparation method provided by the present invention sets the rotation speed and pressure values ​​in the internal mixing process, so that the raw material molecules are more tightly combined and the material distribution is uniform, which solves the problem of eccentric wear of synthetic brake shoes caused by inconsistent wear rate due to uneven material, thereby extending the service life of the brake shoes.

[0112] In the present invention, if the discharging glue temperature is too high, for example, higher than 50°C, the compression modulus of the brake shoe will be too high, resulting in cracks in the use of the brake shoe. If the glue temperature is too low, for example, lower than 40°C, the raw material cannot be formed, and the banburying effect cannot be achieved, resulting in a decrease in various properties of the friction material. It should be noted that in the present invention, the banburying pressure is closely related to the glue temperature. If the banburying pressure is too high, for example, higher than 0.4MPa, the mixing temperature rises sharply, which is not conducive to the dispersion of the adhesive, and the material properties will be affected. Too high pressure will increase the power load of the banbury mixer, and even overload and power failure may occur; if the banburying pressure is too low, for example, lower than 0.2MPa, the material mixing will be uneven, affecting the product quality.

[0113] In a specific embodiment of the present invention, the method for preparing the friction body material further comprises step 3, wherein the friction body material is obtained by crushing and baking in sequence.

[0114] In a specific embodiment of the present invention, step 3 comprises the following steps:

[0115] Step 3a: Crushing: The raw materials after mixing are crushed by a crusher for coarse and fine crushing and then used for later use;

[0116] Step 3b: Baking: Put the crushed material into a curing furnace for baking at a temperature of 60-80° C. for 4-6 hours to obtain the friction body material.

[0117] It should be noted that the baking step in step 3b can reduce the moisture content of the friction body material and prevent the brake shoe tread from cracking during curing.

[0118] In a third aspect, the present invention provides a synthetic brake shoe, comprising the above-mentioned friction material and a shoe back, wherein the friction material is fixed on the shoe back.

[0119] In a fourth aspect, the present invention provides a method for preparing a synthetic brake shoe, comprising the steps of preforming and curing a friction body material and a shoe back.

[0120] In a specific embodiment of the present invention, the preforming step is: using a press to press the baked friction body material through a special mold and the shoe back to form a synthetic brake shoe blank at room temperature, with a press pressure of 100T and a holding time of 2s.

[0121] In a specific embodiment of the present invention, the curing step includes primary curing and secondary curing:

[0122] Primary curing: put the pressed brake shoe blank into the hot pressing mold, set the frame press pressure to 220±10T, set the hot pressing mold heating temperature to 150±10℃, exhaust interval to 18s, exhaust times to 2-6 times, hold the pressure for 600-1200s, then demould and take out the shaped brake shoe;

[0123] Secondary curing: The shaped brake shoe is placed in a curing furnace for secondary curing. The curing temperature is gradually increased from room temperature to 160°C through 80°C-100°C-120°C-130°C-140°C-150°C, and then cooled down with the furnace. The total time is 32-36 hours, which is used to improve the vulcanization effect of the brake shoe and stabilize the internal molecular structure of the friction material.

[0124] The synthetic brake shoe provided by the present invention is prepared from the components through the steps of stirring and kneading to prepare a friction body material, and then the friction body material and the shoe back pressure are synthesized into a synthetic brake shoe. The synthetic brake shoe has light weight, stable friction coefficient, small wear, low noise during braking, high mechanical properties, and can be used for heavy-duty railway trucks, fully ensuring the braking friction and wear performance and mechanical properties of the synthetic brake shoe.

[0125] The preferred embodiments of the present invention are described in detail below to illustrate the principles of the present invention, but are not intended to limit the scope of the present invention.

[0126] Unless otherwise specified, all materials used are commercially available products.

[0127] Example 1

[0128] (1) Preparation method of friction body material. The raw materials of the friction body material are shown in Table 1:

[0129] Step 1: First, stir the phenolic resin and powdered nitrile for the first time, stir for 2 minutes to mix evenly, then add steel fiber, sepiolite, basalt fiber, needle-shaped wollastonite, barium sulfate, calcium carbonate, iron powder, flake graphite, high aluminum powder, potassium feldspar, molybdenum disulfide and antimony trisulfide, stir for the second time, stir for 2 minutes to mix evenly;

[0130] Step 2: The stirred materials are put into the internal mixer at a speed of 26 rpm and a pressure of 0.31 MPa. After stirring for 120 seconds, ethanol and octadecenoic acid are added. The internal mixing conditions remain unchanged. When the rubber temperature rises to 45°C, the lower plug is opened to discharge the materials.

[0131] Step 3a: The raw materials after mixing are crushed by a crusher for use;

[0132] Step 3b: baking in a drying furnace, setting the temperature to 60° C. for 6 hours; obtaining the friction body material.

[0133] (2) Preparation method of synthetic brake shoe:

[0134] Preforming: Use a press machine with a mold to pre-press the shoe back and friction material into a brake shoe blank. The press pressure is 100T and the holding time is 2s.

[0135] Curing: Put the brake shoe blank into the heated mold cavity under the press for primary curing. The press pressure is 230T, the curing time is 600s, the exhaust interval is 18s, the exhaust times are 4 times, the primary curing temperature is 150±10℃, and the brake shoe is initially vulcanized and shaped, then removed from the mold and the wear line is marked; the shaped brake shoe is placed in the curing furnace for secondary curing, and the curing temperature is gradually increased from 80℃ to 160℃.

[0136] Table 1 Composition of raw materials of friction body material of Example 1

[0137]

[0138]

[0139] Example 2

[0140] This embodiment is substantially the same as embodiment 1, except that the internal mixer speed is 30 rpm.

[0141] Example 3

[0142] This embodiment is substantially the same as embodiment 1, except that the internal mixer speed is 20 rpm.

[0143] Example 4

[0144] This embodiment is basically the same as Embodiment 1, except that the upper push bolt pressure value is 0.22 MPa.

[0145] Example 5

[0146] This embodiment is basically the same as Embodiment 1, except that the upper push bolt pressure value is 0.38 MPa.

[0147] Example 6

[0148] This embodiment is basically the same as the embodiment 1, except that when the glue temperature rises to 49°C, the lower ejector plug is opened to discharge the material.

[0149] Example 7

[0150] This embodiment is basically the same as the embodiment 1, except that when the glue temperature rises to 40°C, the lower ejector bolt is opened to discharge the material.

[0151] Example 8

[0152] This example is substantially the same as Example 1, except that the amount of ethanol is 13 g and the amount of octadecenoic acid is 35 g.

[0153] Example 9

[0154] This example is substantially the same as Example 1, except that the amount of ethanol is 43 g and the amount of octadecenoic acid is 5 g.

[0155] Example 10

[0156] This embodiment is substantially the same as embodiment 1, except that the amount of phenolic resin is 256 g and the amount of powdered nitrile is 316 g.

[0157] Comparative Example 1

[0158] This comparative example is substantially the same as Example 1, except that ethanol is not included and the amount of octadecenoic acid is 48 g.

[0159] Comparative Example 2

[0160] This comparative example is basically the same as Example 1, except that octadecenoic acid is not included and the amount of ethanol is 48 g. When octadecenoic acid is not included, the material cannot be formed during the mixing process and the subsequent steps cannot be continued.

[0161] Comparative Example 3

[0162] This comparative example is basically the same as Example 1, except that the first stirring is not performed, but the bonding material, the reinforcing composite material, and the filling material are stirred simultaneously.

[0163] Test Case

[0164] According to the content of "Part 1: Synthetic Brake Shoes" of TB / T 3104.1-2020 Locomotive and Rolling Stock Brake Shoes, friction and wear performance and mechanical performance tests were carried out, and some performance parameter indicators are shown in Table 2. Among them, the average friction coefficient and wear amount experiment was carried out in accordance with the requirements of the brake wear performance experiment in Appendix F of TB / T 3104.1-2020 Locomotive and Rolling Stock Brake Shoes "Part 1: Synthetic Brake Shoes" 1:1 bench test. The test conditions of the average friction coefficient are a braking speed of 125km / h and a braking pressure of 20kN. After the test is completed, the wear amount is calculated based on the weight loss and braking energy. The performance parameter results of the embodiment and the comparative example are shown in Table 3.

[0165] Table 2 Performance parameters

[0166]

[0167] Table 3 Friction and wear properties and mechanical properties parameters of the embodiments and comparative examples

[0168]

[0169]

[0170] It can be seen from Examples 1-10 and Comparative Examples 1-3 that the friction body material of the present invention has an ideal friction coefficient, can achieve control of performance indicators such as hardness and impact strength of the synthetic brake shoe, and can adapt to the requirements of general railway freight cars with different axle weights and running speeds for brake wear performance.

[0171] It can be seen from Example 1 and Comparative Examples 1-3 that in Comparative Example 1, ethanol is not added, the friction coefficient is significantly reduced, the wear amount is significantly increased, the impact strength is significantly reduced, the hardness is also significantly reduced, and the overall performance is significantly deteriorated; in Comparative Example 2, octadecenoic acid is not added, and the subsequent steps cannot be continued; in Comparative Example 3, the adhesive material is not stirred for the first time, the friction coefficient is significantly reduced, the wear amount is significantly increased, the impact strength is reduced, and the overall performance is significantly deteriorated.

[0172] It can be seen from Examples 1-3 that the internal mixer speeds of Examples 2 and 3 are adjusted to 30 rpm and 20 rpm respectively, the friction coefficient is slightly reduced, and the wear amount is slightly increased. Compared with Example 1, the comprehensive performance of Examples 2-3 is reduced.

[0173] It can be seen from Examples 1 and 4-5 that the pressure values ​​of Examples 4 and 5 are adjusted to 0.22Mpa and 0.38MPa respectively. Although Example 4 has a higher friction coefficient and lower wear, its hardness is high (the preferred range of hardness is 80-90), which is already over 90. Under this hardness, the risk of metal inlay in the friction body material increases significantly, and the metal inlay phenomenon will cause hard alloy in the friction body material, thereby damaging the wheel; the friction coefficient of the brake shoe of Example 5 is slightly reduced, the wear is slightly increased, and the hardness is reduced. Compared with Example 1, the comprehensive performance of Examples 4-5 is reduced.

[0174] It can be seen from Example 1 and Example 6-7 that the discharging glue temperature of Example 6 and Example 7 is adjusted to 49°C and 40°C respectively, the compression modulus of Example 6 increases, and the risk of cracks in the brake shoe increases; the friction coefficient of Example 7 is slightly reduced, the wear amount is slightly increased, the impact strength is low, and the pull-off force is low. Compared with Example 1, the comprehensive performance of Example 6-7 is reduced.

[0175] It can be seen from Examples 1 and 8-10 that the dosages of ethanol and octadecenoic acid were adjusted in Examples 8 and 9, respectively, and the dosages of phenolic resin and powdered nitrile were adjusted in Example 10. The friction coefficient of Example 8 was slightly reduced, and the hardness was reduced; the friction coefficient of Example 9 was slightly reduced, and the pull-off force was reduced; the friction coefficient of Example 10 was slightly reduced, and the bending strength was reduced. Compared with Example 1, the comprehensive performance of Examples 8-10 was reduced.

[0176] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.

Claims

1. A friction material, characterized in that: The composition comprises the following components or is made from raw materials comprising the following components: Adhesive material: 46-68 parts by weight; Reinforcement material: 48-88 parts by weight; Filling material: 97-167 parts by weight; Auxiliary materials: 1.5-9 parts by weight, Wherein, the bonding material comprises phenolic resin and powdered nitrile rubber, and the auxiliary agent comprises ethanol and octadecenoic acid.

2. The friction body material according to claim 1, characterized in that: The amount of bonding material is 54-60 parts by weight; and / or, the amount of the reinforcing material is 62-76 parts by weight; and / or, the amount of the filler material is 118-147 parts by weight; And / or, the dosage of auxiliary agents and auxiliary materials is 4-7.5 parts by weight.

3. The friction body material according to claim 1 or 2, characterized in that: In the friction body material, The amount of phenolic resin is 23-34 parts by weight, preferably 27-30 parts by weight; The amount of powdered nitrile rubber is 23-34 parts by weight, preferably 27-30 parts by weight. And / or, the hexamethylenetetramine content of the phenolic resin is 7wt.%-8wt.%, the free phenol content is ≤1wt.%, the polymerization time is 40-70s at 150°C, and the particle size is 150-250 mesh; And / or, the powdered nitrile rubber has a combined acrylonitrile content of 36wt.%-40wt.%, and a particle size of 35-45 mesh.

4. The friction body material according to claim 1 or 2, characterized in that: In the friction body material, The amount of ethanol is 1-6 parts by weight, preferably 3-5 parts by weight; The amount of octadecenoic acid used is 0.5-3 parts by weight, preferably 1-2.5 parts by weight.

5. The friction body material according to claim 1 or 2, characterized in that: The reinforcing material comprises at least one of sepiolite, steel fiber, mineral fiber, and needle-shaped wollastonite; Preferably, the reinforcing material comprises sepiolite, steel fiber, mineral fiber and needle-shaped wollastonite, wherein: The amount of sepiolite is 25-35 parts by weight, preferably 28-32 parts by weight; The amount of steel fiber is 10-20 parts by weight, preferably 14-17 parts by weight; The amount of mineral fiber is 6-16 parts by weight, preferably 10-13 parts by weight; The amount of needle-shaped wollastonite used is 7-17 parts by weight, preferably 10-14 parts by weight.

6. The friction body material according to claim 1 or 2, characterized in that: The filling material comprises at least one of calcium carbonate, barium sulfate, reduced iron powder, graphite, high aluminum powder, potassium feldspar, molybdenum disulfide and antimony trisulfide; Preferably, the filling material includes calcium carbonate, barium sulfate, reduced iron powder, graphite, high aluminum powder, potassium feldspar, molybdenum disulfide and antimony trisulfide, wherein: The amount of calcium carbonate is 5-15 parts by weight, preferably 8-12 parts by weight; The amount of barium sulfate is 5-15 parts by weight, preferably 8-12 parts by weight; The amount of reduced iron powder is 21-31 parts by weight, preferably 24-28 parts by weight; The amount of graphite is 4-14 parts by weight, preferably 8-11 parts by weight; The amount of high aluminum powder is 11-21 parts by weight, preferably 14-18 parts by weight; The amount of potassium feldspar is 48-58 parts by weight, preferably 51-55 parts by weight; The amount of molybdenum disulfide is 2-8 parts by weight, preferably 3-7 parts by weight; The amount of antimony trisulfide used is 1-5 parts by weight, preferably 2-4 parts by weight.

7. A method for preparing the friction material according to any one of claims 1 to 6, characterized in that: The steps include: Step 1: Stirring the bonding material including phenolic resin and powdered nitrile rubber for the first time, and then adding reinforcing material and filling material and stirring for the second time; Step 2: Carry out the first stage of internal mixing, then add auxiliary agents and materials to carry out the second stage of internal mixing, and then discharge the material.

8. The preparation method according to claim 7, characterized in that: In step 1, the duration of the first stirring and the second stirring is the same or different, and each is independently 2-5 minutes.

9. The preparation method according to any one of claims 7-8, characterized in that: In step 2, the conditions of the first stage of banburying include: a rotation speed of 20-30 rpm, preferably 24-27 rpm; a pressure of 0.2-0.4 MPa, preferably 0.25-0.35 MPa; and a banburying time of 120-180 s; And / or, in step 2, the conditions of the second stage of banburying include: a rotation speed of 20-30 rpm, preferably 24-27 rpm; a pressure of 0.2-0.4 MPa, preferably 0.25-0.35 MPa, And / or, in step 2, the temperature of the discharged glue is 40-50°C, preferably 42-45°C.

10. A synthetic brake shoe, characterized in that: The invention comprises the friction material according to any one of claims 1 to 6 or the friction material prepared by the preparation method according to any one of claims 7 to 9 and a tile back, wherein the friction material is fixed on the tile back.

Citation Information

Patent Citations

  • High-friction synthetic brake shoe for high-power XHN5 locomotive, preparation method and application thereof

    CN102401052A

  • Rubber modified multielement resin material for disc brake pad and purposes

    CN107061574A

  • Preparation method of glass fiber reinforced ABS (Acrylonitrile Butadiene Styrene) composite material

    CN116535701A